Examining Relationships between Gender, Opioid Dependence, and Distress Tolerance among Patients in Substance Use Disorder Treatment. (1st May 2020) - Tull, Matthew T.; Edmonds, Keith A.; Forbes, Courtney N.; Richmond, Julia R.; Rose, Jason P.; Anestis, Michael D.; Gratz, Kim L.
Abstract: Background : Opioid abuse/dependence is associated with multiple negative outcomes relative to other forms of substance abuse/dependence, including relapse. Research identifying modifiable characteristics associated with opioid dependence and associated negative outcomes may inform the development of targeted interventions for this high-risk population. One factor warranting investigation is low distress tolerance (DT). Purpose/Objectives : In a sample of patients in substance use disorder (SUD) treatment, the present study examined DT levels among patients with current opioid dependence versus no history of opioid dependence, as well as the moderating role of gender. We predicted that patients with opioid dependence would exhibit lower DT than those without a history of opioid dependence, and that women with opioid dependence would exhibit lower levels of DT than men with opioid dependence. Methods : A sample of 203 patients in residential SUD treatment were administered a series of diagnostic interviews and a behavioral measure of DT. Results : DT did not differ significantly as a function of opioid dependence. However, there was a significant opioid dependence by gender interaction, such that men with current opioid dependence exhibited significantly lower levels of DT than women with opioid dependence and men without a history of opioid dependence. Conclusions/Importance : Findings highlight a modifiable characteristic associated with opioid dependence among men that may be targeted in interventions.